Dynamic MRI in the evaluation of the spine: state of the art - Michelini, Giulia; Corridore, Antonella; Torlone, Silvia; Bruno, Federico; Marsecano, Claudia; Capasso, Raffaella; Caranci, Ferdinando; Barile, Antonio; Masciocchi, Carlo; Splendiani, Alessandra (Acta Biomedica Atenei Parmensis, 2018)
Introduction: Degenerative disease of the spine is a generic term encompassing a wide range of different disease processes, which leads to spinal instability; traumatic/neoplastic events can accelerate this aging process. Therefore, the dynamic nature of the spine and its mobility across multiple segments is difficult to depict with any single imaging modality. Methods: A review of PubMed databases for articles published about kMRI in patients with cervical and lumbar spinal desease was performed. We focused on the physiopathological changes in the transition from supine to upright position in spine instability. Discussion: Until a few years ago, X-ray was the only imaging modality for the spine in the upright position. Of the imaging techniques currently available, MRI provides the greatest range of information and the most accurate delineation of soft-tissue and osseous structures. Conventional MRI examinations of the spine usually are performed in supine position, in functional rest, but the lumbar spine instability is often shown only by upright standing. This can result in negative findings, even in the presence of symptoms. Regardless, the final result is distorted. To overcome this limitation, Kinetic MRI (kMRI) can image patients in a weight-bearing position and in ﬂexed and extended positions, thus revealing abnormalities that are missed by traditional MRI studies. Conclusion: Despite some limitations, the upright MRI can be a complementary investigation to the traditional methods when there are negative results in conventional MRI in symptomatic patients or when surgical therapy is scheduled.